2002
DOI: 10.1111/1468-5957.00475
|View full text |Cite
|
Sign up to set email alerts
|

The Market for External Audit Services in the Public Sector: An Empirical Analysis of NHS Trusts

Abstract: This study investigates the market for audit services in the UK National Health Service (NHS). The market has a number of interesting features, including the presence of the Audit Commission as a regulator, appointer and provider of audit services. Following a theoretical overview of audit pricing in the NHS, evidence is provided on the behaviour of private sector auditors in an environment where audit risk characteristics differ from the private sector. The research also investigates, for the first time in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
72
2
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(85 citation statements)
references
References 24 publications
(80 reference statements)
7
72
2
4
Order By: Relevance
“…For quoted companies, Chan et al (1993) found a premium of 36.7%, Ezzamel et al (1996), 23.5%, and for independent unquoted firms Brinn et al (1994) found a 28.0% premium. By contrast, neither Che-Ahmad and Houghton (1996), in their study of medium-sized UK companies, nor Clatworthy et al (2000) in their study of UK National Health Service Trusts found any evidence of a large audit firm premium.…”
Section: Discussionmentioning
confidence: 87%
“…For quoted companies, Chan et al (1993) found a premium of 36.7%, Ezzamel et al (1996), 23.5%, and for independent unquoted firms Brinn et al (1994) found a 28.0% premium. By contrast, neither Che-Ahmad and Houghton (1996), in their study of medium-sized UK companies, nor Clatworthy et al (2000) in their study of UK National Health Service Trusts found any evidence of a large audit firm premium.…”
Section: Discussionmentioning
confidence: 87%
“…There have been many research studies examining the nature of the company fee market, but few have investigated the public sector audit market (e.g. Beck and Barefield, 1986;Baber et al, 1987;Rubin, 1988;Copley, 1989;Beattie et al, 2002) and only one has examined NHS audit fees (Clatworthy et al, 2002).…”
Section: The Audit Framework In the Nhsmentioning
confidence: 99%
“…10 Clatworthy et al (2002) include comparisons of auditor type but not within individual audit firms and not using sub-samples. The use of our auditor size classes provides a richer test of the association between auditor size and audit fees than in Clatworthy et al (2002).…”
Section: Set Y Relates To Total Auditor Remunerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some empirical studies find a negative relation between audit and non-audit fees (Clatworthy et al, 2002;Fields et al, 2004), or report a lack of association (Abdel-Khalik, 1990). Studies using simultaneous equation methods accounting for bi-directional causality report a positive (Antle et al, 2006;McMeeking et al, 2006) or non-association (Whisenant et al, 2003;Hay et al, 2006a) between audit and non-audit fees.…”
Section: Joint Provision Of Audit and Other Services By The Statutorymentioning
confidence: 99%